The Exploring the Opportunities: Implementing Mind Mapping in Seventh Grade Reading Students of SMP Terpadu Madinatul Ulum - Sari, Verryna Rosita; Hayuningtyas, Nina (Critical Review of English-Arabic World Journal, 2023)
The purpose of this study is to outline how mind maps are used to help middle school students learn to read. Case study design is a qualitative research approach used in this research. The research was carried out at SMP Terpadu Madinatul Ulum. Observations, interviews, and document reviews were used to collect data. Meanwhile, triangulation of sources and techniques is used in data validation. Based on data analysis and student comments, the findings of this study indicate that mind maps enhance vocabulary acquisition by offering a visual representation of the content of the text.